Biomarkers for evaluating response to chemotherapy in metastatic breast cancer patients - Mohammed Ali, Nidhal A.K.; Younis, Rehab M.; Salai, Jangi S. (Journal of the Faculty of Medicine Baghdad, 2017)
Background: Although, different protocols of chemotherapy are recommended for the treatment of metastatic breast cancer, still response rates are variable. Objectives: The aim of this study is to investigate the effects and correlation of different chemotherapy administered to metastatic breast cancer patients on serum levels of some biomarkers. Patients and methods: Thirty metastatic breast cancer patients were enrolled in the study. The patients received different protocols of chemotherapy. Blood samples were taken from the patients before and after the last cycle of each protocol and from 20 healthy control and serum levels of biomarkers IL-6, leptin, CA 15-3 and p53 were estimated by Elisa. Results: The mean serum levels of IL-6, leptin, CA 15-3 and p53 were significantly (P ≤ 0.01) higher in patients before and after chemotherapy compared to controls. A significant (P≤0.01) higher mean levels of IL-6, leptin and p53 was found in the patients after chemotherapy compared to before chemotherapy with the exception of mean serum levels of CA 15-3 that did not differed significantly (P≥0.174) after chemotherapy compared to before chemotherapy. A significant correlation was found between hormone status and the mean serum level of leptin and between the mean serum levels of CA15-3 and IL-6. Conclusion: The results highlights that the biomarkers IL-6, leptin, CA 15-3, p53 play a role in breast cancer progression and metastasis and could be helpful in predicting and monitoring chemosensitivity to these chemotherapeutic drugs.